Care home residents' quality of life and its association with CQC ratings and workforce issues: the MiCareHQ mixed-methods study - Ann-Marie Towers; Nick Smith; Stephen Allan; Florin Vadean; Grace Collins; Stacey Rand; Jennifer Bostock; Helen Ramsbottom; Julien Forder; Stefania Lanza; Jackie Cassell (National Institute for Health Research, 2021)
Background: Care home staff have a critical bearing on quality. The staff employed, the training they receive and how well they identify and manage residents' needs are likely to influence outcomes. The Care Act 2014 (Great Britain. The Care Act 2014. London: The Stationery Office; 2014) requires services to improve 'well-being', but many residents cannot self-report and are at risk of exclusion from giving their views. The Adult Social Care Outcomes Toolkit enables social care-related quality of life to be measured using a mixed-methods approach. There is currently no equivalent way of measuring aspects of residents' health-related quality of life. We developed new tools for measuring pain, anxiety and depression using a mixed-methods approach. We also explored the relationship between care home quality, residents' outcomes, and the skill mix and employment conditions of the workforce who support them. Objectives: The objectives were to develop and test measures of pain, anxiety and depression for residents unable to self-report; to assess the extent to which regulator quality ratings reflect residents' care-related quality of life; and to assess the relationship between aspects of the staffing of care homes and the quality of care homes. Design: This was a mixed-methods study. Setting: The setting was care homes for older adults in England. Participants: Care home residents participated. Results: Three measures of pain, anxiety and low mood were developed and tested, using a mixed-methods approach, with 182 care home residents in 20 care homes (nursing and residential). Psychometric testing found that the measures had good construct validity. The mixed-methods approach was both feasible and necessary with this population, as the majority of residents could not self-report. Using a combined data set (n = 475 residents in 54 homes) from this study and the Measuring Outcomes in Care Homes study (Towers AM, Palmer S, Smith N, Collins G, Allan S. A cross-sectional study exploring the relationship between regulator quality ratings and care home residents' quality of life in England. Health Qual Life Outcomes 2019;17:22) we found a significant positive association between residents' social care-related quality of life and regulator (i.e. Care Quality Commission) quality ratings. Multivariate regression revealed that homes rated 'good/outstanding' are associated with a 12% improvement in mean current social care-related quality of life among residents who have higher levels of dependency. Secondary data analysis of a large, national sample of care homes over time assessed the impact of staffing and employment conditions on Care Quality Commission quality ratings. Higher wages and a higher prevalence of training in both dementia and dignity-/person-centred care were positively associated with care quality, whereas high staff turnover and job vacancy rates had a significant negative association. A 10% increase in the average care worker wage increased the likelihood of a 'good/outstanding' rating by 7%. Limitations: No care homes rated as inadequate were recruited to the study. Conclusions: The most dependent residents gain the most from homes rated 'good/outstanding'. However, measuring the needs and outcomes of these residents is challenging, as many cannot self-report. A mixed-methods approach can reduce methodological exclusion and an over-reliance on proxies. Improving working conditions and reducing staff turnover may be associated with better outcomes for residents. Future work: Further work is required to explore the relationship between pain, anxiety and low mood and other indicators of care homes quality and to examine the relationship between wages, training and social care outcomes. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 9, No. 19. See the NIHR Journals Library website for further project information.